2022
DOI: 10.1007/s40089-022-00379-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high efficiency coronavirus filter using activated carbon nanoparticles

Abstract: In this study design and fabrication of coronavirus filter based on the cellulose and carbon nanomaterials have been investigated. Particulate matter (PM) corona virus has attracted a lot of attention due to its great threat to human health. Nanoparticles are intertwined with fibers and form highly porous air filter paper. The structure of the filter has been characterized using scanning electron microscope (SEM) and Brunauer–Emmett–Teller (BET) analysis. In addition, by optimization with activated carbon (AC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The outcomes exhibited the decreasing size of the holes through nanomaterials in the filter to 30 nm. These carbon-based materials showed that the activated carbon NPs have a good potential to be applied for mask fabrication [103] .…”
Section: Carbon-based Nanomaterials Against Sars-cov-2: Synthesis Dia...mentioning
confidence: 99%
“…The outcomes exhibited the decreasing size of the holes through nanomaterials in the filter to 30 nm. These carbon-based materials showed that the activated carbon NPs have a good potential to be applied for mask fabrication [103] .…”
Section: Carbon-based Nanomaterials Against Sars-cov-2: Synthesis Dia...mentioning
confidence: 99%
“…[63][64][65][66][67][68] Nanomaterials and nanocomposites are receiving more attention in making energy storage devices, sensors, and different applications. [69][70][71][72][73][74][75] In this review, the developments of Ni material/carbon nanomaterial-based supercapacitors for 2022-2023 publications (Scopus) are studied and compared. We have discussed the specific capacitance, power density, energy density, cycling stability, and rate capability of Ni-materials/carbon nanocomposites in supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%